Hello!
First of all, let's rewrite some square roots and their values:
![\begin{gathered} √(1)=1 \\ √(4)=2 \\ √(9)=3 \\ √(16)=4 \\ √(25)=5 \\ √(36)=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mnv80aksufju5kglp9weex4nfivbrdezjt.png)
Knowing it, let's analyze your problem:
We know that the square root of 36 is 6.
Let's try to rewrite this expression but in another way, also obtaining the same result 6.
Let's do it:
![\begin{gathered} √(4)\cdot√(9)=√(36) \\ 2\cdot3=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r60w9nhtjnuteqs9zwkkseth2xfqbe239i.png)
Answer:
![√(4)\cdot√(9)=√(36)](https://img.qammunity.org/2023/formulas/mathematics/college/mj9swy3fic710ngvxymdb4gadj2o8fqihn.png)